Chemical constituents of the bark of ryparosa kunstleri (Flacourtiaceae) - Shaari, Khozirah; Waterman, Peter G. (Universiti Putra Malaysia Press, 1997)
The bark of Ryparosa kunstleri yielded the triterpenes friedelin, trichadenic acid B, and the new 3B-p-coumaroyl trichadenic acid as its major constituents. Stictic acid, a depsidone, was also isolated but was deduced to be a contaminant.